Tular Nalar Sekolah Kebangsaan Mencegah Hoaks dan Ujaran Kebencian di Kabupaten Majene - Arie Arma Arsyad; Dewi Sartika; St. Mutia Alfiyanti Muhiddin; Nurfitra Yanto; Hasanuddin Hasanuddin (JKM: Jurnal Kemitraan Masyarakat, 2023)
The spread of hoaxes in Indonesia is a serious problem. According to survey data conducted by the Katadata Insight Center and Kominfo in 2021, it shows that the elderly group aged 55-70 years is only 3.6 percent of internet users. Meanwhile, the millennial generation (23-38 years) is 43.8%, generation Z (13-22 years) is 28.6% and generation X (39-54 years) is 23.9%. The problem in society today is the lack of ability to digest correct information. So the government needs to provide teaching or literacy in fact-checking materials and media literacy. This is related to the many hoaxes, fake news and slander that are circulating in society. Therefore, the Tular Reasoning Activity was held as a form of initial prevention for the people of Majene Regency in facing the 2024 ELECTION, especially for the elderly and also the younger generation so that they know how to distinguish between facts and hoaxes circulating through their gadgets and digital devices. Through learning materials from media and digital literacy facilitators, the community will come together to find out the truth of news, be responsive in seeing the truth, and be tough in fighting hoaxes.